Ethics theory and contemporary issues - Fiala, Andrew; MacKinnon, Barbara (Cengage Learning, 2023)
"We live in a rapidly changing and contentious time. There are conflicts of value all around us and serious debates about contemporary issues, including health care, abortion, euthanasia, biotechnologies, social justice, racial and economic inequality, global poverty, gender and sexuality, crime and punishment, war and peace, environmentalism, and our treatment of animals. In the background of these issues are conflicting theories of ethics. This book provides an overview of ongoing and perennial discussions about ethical theory, while also showing how ethical judgment might apply to a variety of contemporary issues. It is intended for students who are learning to think critically about ethics and who want to learn more about contemporary moral questions. Readers of this book will obtain a comprehensive introduction to ethics in theory and practice. We hope that readers will gain critical thinking skills and a deeper understanding of moral issues that can be employed in their own lives"--